TET2 Deficiency Inhibits Mesoderm and Hematopoietic Differentiation in Human Embryonic Stem Cells. (15th July 2014) - Langlois, Thierry; da Costa Reis Monte-Mor, Barbara; Lenglet, Gaëlle; Droin, Nathalie; Marty, Caroline; Le Couédic, Jean-Pierre; Almire, Carole; Auger, Nathalie; Mercher, Thomas; Delhommeau, François; Christensen, Jesper; Helin, Kristian; et al.
Abstract: Ten-eleven-translocation 2 (TET2) belongs to the TET protein family that catalyzes the conversion of 5-methylcytosine into 5-hydroxymethylcytosine and plays a central role in normal and malignant adult hematopoiesis. Yet the role of TET2 in human hematopoietic development remains largely unknown. Here, we show that TET2 expression is low in human embryonic stem cell (ESC) lines and increases during hematopoietic differentiation. shRNA-mediated TET2 knockdown had no effect on the pluripotency of various ESCs. However, it skewed their differentiation into neuroectoderm at the expense of endoderm and mesoderm both in vitro and in vivo. These effects were rescued by reintroducing the targeted TET2 protein. Moreover, TET2-driven differentiation was dependent on NANOG transcriptional factor. Indeed, TET2 bound to NANOG promoter and in TET2-deficient cells the methylation of the NANOG promoter correlated with a decreased in NANOG expression. The altered differentiation resulting from TET2 knockdown in ESCs led to a decrease in both the number and the cloning capacities of hematopoietic progenitors. These defects were due to an increased apoptosis and an altered gene expression profile, including abnormal expression of neuronal genes. Intriguingly, when TET2 was knockdown in hematopoietic cells, it increased hematopoietic development. In conclusion, our work suggests that TET2 is involved in different stages of human embryonic development, including induction of the mesoderm and hematopoietic differentiation. Stem Cells 2014;32:2084–2097